Chelate type solvent-free low-surface nanometer heavy anti-corrosion coating and preparation method thereof

By adopting chelating solvent-free low-surface nanoheavy anticorrosion coating, using the design of high crosslink density and double-layer passivation film, the problem of poor anticorrosion quality during construction in harsh environments is solved, and excellent adhesion, corrosion resistance and construction performance is achieved, and it is a green and environmentally friendly product.

CN119735998APending Publication Date: 2025-04-01WUXI HUADONG ZINDN TECH

Patent Information

Application Number
CN202411961470.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

When constructed in harsh environments, existing anticorrosion coatings are susceptible to factors such as water and rust, resulting in poor anticorrosion quality and high pretreatment requirements, which limits the flexibility of construction.

Method used

The chelated solvent-free low-surface nano-heavy anticorrosion coating is used. The coating consists of epoxy resin, modified amine curing agent, anti-rust pigment, nano-filler and scale filler. Through the design of a high crosslinking density and the double-layer passivation film, excellent adhesion, corrosion resistance and construction performance are achieved.

Benefits of technology

The coating exhibits excellent adhesion and curing properties on water- and rusted substrates, has excellent wear resistance, scratch resistance and impact resistance, and is also low in VOC content, making it a green and environmentally friendly product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735998A_ABST
    Figure CN119735998A_ABST
Patent Text Reader

Abstract

The invention discloses a chelated solvent-free low-surface nanometer heavy anti-corrosion coating and a preparation method thereof, the chelated solvent-free low-surface nanometer heavy anti-corrosion coating comprises a component A and a component B, and the weight ratio of the component A to the component B is (4-6): 1; the raw materials are in parts by weight; the component A is prepared from 20 to 40 parts of epoxy resin, 10 to 15 parts of reactive diluent, 0.5 to 0.9 part of dispersing agent, 0.5 to 1.5 parts of rheological additive, 0.1 to 0.5 part of defoaming agent, 10 to 30 parts of filler, 10 to 20 parts of anti-rust pigment, 10 to 20 parts of scale filler, 10 to 20 parts of nano filler and 1 to 4 parts of chelating additive; the component B comprises 100 parts of a modified amine curing agent. The chelating solvent-free low-surface nanometer heavy anti-corrosion coating disclosed by the invention has the functions of rust conversion and rust stabilization, and can be used for construction with rust and water. Meanwhile, a paint film is excellent in compactness and shielding performance, safe and environmentally friendly, the voc content is lower than 10 g / L, and the paint belongs to a green product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional coatings, in particular to a chelated solvent-free low-surface nano heavy-duty anticorrosive coating and a preparation method thereof. Background Art

[0002] In 2024, the global anti-corrosion coating market reached $13.6 billion, with a CAGR of 4% from 2024 to 2029. With the promotion of environmental protection regulations, the demand for environmentally friendly anti-corrosion coatings continues to increase, especially high-performance, low-VOC products. In addition, the anti-corrosion coating industry will be more diversified and personalized to meet the needs of different industries and scenarios. The existing coating system generally has high requirements for pre-treatment, such as: blast cleaning to Sa2.5 level (ISO8501-1), surface roughness reaches Rz30μm~75μm, and it is best to apply primer within 4 hours after blast cleaning. And the environmental humidity requirement during construction is generally not more than 85%. However, these harsh conditions and environments are inevitable at the coating site, especially for most maintenance projects, rust and old coatings due to inadequate pre-treatment; high humidity or clear water in the construction environment; or water and rust caused by water sandblasting, etc., which directly affect the final anti-corrosion quality of the coating. Summary of the invention

[0003] In view of the above problems existing in the prior art, the present invention provides a chelate-type solvent-free low-surface nano heavy anti-corrosion coating and a preparation method thereof. The chelate-type solvent-free low-surface nano heavy anti-corrosion coating of the present invention has the functions of rust removal and rust stabilization, and can be applied with rust and water. At the same time, the paint film has excellent density and shielding performance, is safe and environmentally friendly, and the VOC content is less than 10g / L, which is a green product.

[0004] The technical solution of the present invention is as follows:

[0005] The first object of the present invention is to provide a chelate-type solvent-free low-surface nano heavy anticorrosive coating, comprising component A and component B, wherein the weight ratio of component A to component B is 4-6:1; the raw materials of each component and the weight proportion of each raw material are:

[0006] Component A: 20-40 parts of epoxy resin, 10-15 parts of active diluent, 0.5-0.9 parts of dispersant, 0.5-1.5 parts of rheological additive, 0.1-0.5 parts of defoamer, 10-20 parts of anti-rust pigment, 10-20 parts of flake filler, 10-20 parts of nano filler, 1-4 parts of chelating agent;

[0007] Component B: 100 parts of modified amine curing agent.

[0008] In one embodiment of the present invention, the preparation method of the modified amine curing agent is: m-phenylenediamine and nonylphenol are uniformly mixed and reacted with formaldehyde solution under condensation reflux conditions, water is removed by reduced pressure distillation during the reaction, and finally a high temperature reaction is performed to obtain the modified amine curing agent.

[0009] In one embodiment of the present invention, the molar ratio of m-xylylenediamine, nonylphenol and formaldehyde is 1.2-1.6:1.0-1.4:0.6-1.0; and the mass concentration of the formaldehyde solution is 36-38%.

[0010] In one embodiment of the present invention, the temperature of the condensation reflux is 90-110°C, and the reaction time is 3.5-4h; the temperature of the high temperature reaction is: 140-150°C.

[0011] In one embodiment of the present invention, the specific synthesis steps of the modified amine curing agent are: after mixing the measured m-phenylenediamine and nonylphenol, add them into a three-necked flask equipped with a stirring rod, a thermometer, and a constant pressure dropping funnel, add formaldehyde solution at 80°C, control the formaldehyde dropping speed, and add it in batches: after the addition, heat up, condense and reflux for 4h, connect a vacuum pump to perform reduced pressure distillation to remove water, and gradually increase the vacuum degree in the reaction flask. When the fraction is small, increase the temperature in the reaction flask to 150°C, stop distillation, and obtain the modified amine curing agent.

[0012] In one embodiment of the present invention, the modified amine curing agent contains a large amount of highly hydrophobic groups such as C9 fatty chains and benzene rings, so that the coating will not be poorly cured or unable to cure due to the dissolution of the fatty amine in water. At the same time, the paint film using the curing agent has excellent physical and mechanical properties and can also show excellent curing performance underwater or in a humid environment.

[0013] In one embodiment of the present invention, the epoxy resin is one of Phoenix 618, Nanya 128, Sanmu 828 and Sanmu 827. It is 100% solid, does not contain organic solvents, and its main component is E51 type liquid epoxy resin.

[0014] In one embodiment of the present invention, the active diluent is a bifunctional active diluent, such as one or more of Naisu RAL602, Prekai PRO-602, and Yuanbang HK-622. The active diluent can reduce the viscosity of the entire system and prolong the reaction speed of the liquid epoxy and the modified amine, thereby increasing the coating construction time.

[0015] In one embodiment of the present invention, the dispersant is BYK9076.

[0016] In one embodiment of the present invention, the rheological additive is Arkema wax powder Crayvallac SLT, the main component of which is fatty acid amide, which changes from a powder state to a fibrous interactive network structure during the activation process, giving the system excellent anti-settling performance and anti-sagging performance.

[0017] In one embodiment of the present invention, the defoaming agent is Deqian 6800.

[0018] In one embodiment of the present invention, the anti-rust pigment is one or more of zinc phosphate, aluminum tripolyphosphate, zinc phosphomolybdate, red iron, and mica iron oxide.

[0019] Preferably, the anti-rust pigment is a chemically inhibited anti-rust pigment, such as one or more of zinc phosphate, aluminum tripolyphosphate, zinc phosphomolybdate, dihydrogen aluminum tripolyphosphate, and super phosphorus zinc white.

[0020] Phosphorus zinc white: mainly composed of phosphate and borate.

[0021] In one embodiment of the present invention, the flake filler is a flaky glass flake with a thickness of 5 microns.

[0022] In one embodiment of the present invention, the nano filler is one or more of nano zinc oxide, nano iron oxide, nano titanium oxide, and nano sodium silicate.

[0023] In one embodiment of the present invention, the chelating aid is Korrodur, a rust converter produced by German Schwegmann and represented by Shanghai Yingshui Trading.

[0024] The second object of the present invention is to provide a method for preparing the above-mentioned chelated solvent-free low-surface nano heavy anti-corrosion coating, comprising the following steps:

[0025] The preparation method of component A is as follows:

[0026] 1) Add 10-15 parts of active diluent and 0.5-0.9 parts of dispersant into a batching kettle, stir at 500-700 rpm for 3-5 minutes until uniformly dispersed; add 20-40 parts of epoxy resin, stir at 300-600 rpm for 3-5 minutes until uniformly dispersed;

[0027] 2) Add 0.5-1.5 parts of rheological additive, disperse at 1000-1500 rpm for 20 minutes, control the temperature at 40-55°C, and stop to keep warm for 30 minutes;

[0028] 3) Add 10-20 parts of anti-rust pigment and 10-20 parts of nano filler, stir at 800-1000 rpm for 30 minutes, and disperse to a fineness of less than 60 μm;

[0029] 4) Add 10-20 parts of flaky filler, 0.1-0.5 parts of defoaming agent, and 1-4 parts of chelating agent, and stir at a speed of 600-1000 rpm for 5-10 minutes until uniformly dispersed to obtain component A;

[0030] When in use, the components A and B are mixed evenly in a weight ratio of 4-6:1 to obtain a chelating type solvent-free low-surface nano heavy anti-corrosion coating.

[0031] The beneficial technical effects of the present invention are:

[0032] (1) Since the epoxy resin molecular structure contains a large number of polar groups such as hydroxyl and ether groups, extremely strong chemical bonds are formed during the curing process, ensuring excellent adhesion between the coating and the substrate.

[0033] (2) After cross-linking and curing, it can form a smooth coating similar to porcelain enamel. Due to the high cross-linking density and the benzene ring structure in the molecular chain, the coating is hard and flexible, with excellent wear resistance, scratch resistance and impact resistance.

[0034] (3) The shrinkage rate during the reaction curing process is extremely low, and it has the characteristics of thick film formation in one time, good edge coverage, small internal stress, and not easy to crack.

[0035] (4) The highly cross-linked coating has excellent chemical resistance and can withstand long-term immersion in seawater, moderate acids, alkalis, salts, various oils, aliphatic hydrocarbons and other chemicals.

[0036] (5) KORRODUR will transform with the surface oxide layer, and the trivalent iron will be converted into divalent iron. Then the chelating agent component of KORRODUR and the divalent iron will form an iron chelate that firmly adheres to the surface of the substrate. This strengthens the adhesion between the coating, rust and substrate, and the final pull-off adhesion reaches more than 9MPa.

[0037] (6) The present invention uses a bifunctional active diluent. During the coating reaction process, the diluent has two functional groups, which can react with amines to form a cross-linked structure to enhance the density of the coating and improve the corrosion resistance of the coating. At the same time, the rheological properties and viscosity of the coating are adjusted to obtain better coating properties.

[0038] (7) The present invention uses glass flakes as anti-corrosion fillers, which can significantly improve the anti-corrosion performance of the coating. Its unique layered structure can effectively block the erosion of water and chemical solvents, reduce the penetration rate of the medium, and thus extend the service life of the coating. At the same time, it can enhance the wear resistance of the coating, so that it remains intact in high flow or mechanical friction environments, thereby enhancing the wear resistance and corrosion resistance of the coating.

[0039] (8) The nanofiller used in the present invention improves the mechanical properties, heat resistance and corrosion resistance of the material by increasing the surface area and barrier effect. Nano titanium can fill the micropores and micro cracks in the coating to form a barrier effect, preventing the invasion of harmful substances from the outside, thereby improving the corrosion resistance of the coating.

[0040] (9) The anti-rust pigment used in the present invention can have a stronger chelating force with various metal ions, forming an excellent passivation film on the surface of the coated object, and has a strong inhibitory effect on the corrosion of steel and light metals, thereby improving the corrosion resistance of the coating.

[0041] The chelating solvent-free low-surface nano heavy anti-corrosion coating of the present invention adopts a liquid epoxy system with high cross-linking density, and cooperates with flaky glass flakes and nano fillers to form a paint film with super shielding performance; chelating additives and anti-rust pigments are used to form a double-layer passivation film on the surface of the substrate, which strengthens the adhesion and improves the anti-corrosion performance. Finally, through the excellent coating and construction performance of the bifunctional active diluent or. Finally, with the super hydrophobic modified amine curing agent, excellent adhesion, curing and construction can be achieved on water- and rust-containing substrates. Make the VOC content of the entire system less than 10g / L. It is a green, safe and environmentally friendly product. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 Schematic diagram of the synthesis principle of modified amine curing agent.

[0043] Figure 2 A rusty substrate was used to test pull adhesion for the examples.

[0044] Figure 3 For the example, the workability was tested on a wet and rusty substrate.

[0045] Figure 4 The following are the salt spray resistance test results of the coating prepared in Example 6.

[0046] Figure 5 This is the situation of the coating prepared in Example 7 being applied and cured with water. DETAILED DESCRIPTION

[0047] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments.

[0048] Example 1

[0049] A method for preparing a modified amine curing agent comprises the following steps:

[0050] Mix the measured m-phenylenediamine and nonylphenol and add them to a three-necked flask equipped with a stirring rod, a thermometer, and a constant pressure dropping funnel. Add a 38% formaldehyde solution at 80°C, control the formaldehyde dropping speed, and add it in batches; after the addition, heat up, condense and reflux for 4 hours, connect a vacuum pump to perform reduced pressure distillation to remove water, and gradually increase the vacuum degree in the reaction flask. When the fraction is small, increase the temperature in the reaction flask to 150°C, stop distillation, and obtain the modified amine curing agent.

[0051] In this embodiment, the molar ratio of m-xylylenediamine, nonylphenol and formaldehyde is 1.3:1.2:0.7.

[0052] Example 2

[0053] A method for preparing a modified amine curing agent comprises the following steps:

[0054] Mix the measured m-phenylenediamine and nonylphenol and add them to a three-necked flask equipped with a stirring rod, a thermometer, and a constant pressure dropping funnel. Add a 38% formaldehyde solution at 80°C, control the formaldehyde dropping speed, and add it in batches; after the addition, heat up, condense and reflux for 4 hours, connect a vacuum pump to perform reduced pressure distillation to remove water, and gradually increase the vacuum degree in the reaction flask. When the fraction is small, increase the temperature in the reaction flask to 150°C, stop distillation, and obtain the modified amine curing agent.

[0055] The molar ratio of m-phenylenediamine, nonylphenol and formaldehyde is 1.4:1.2:0.8.

[0056] Example 3

[0057] A method for preparing a modified amine curing agent comprises the following steps:

[0058] Mix the measured m-phenylenediamine and nonylphenol and add them to a three-necked flask equipped with a stirring rod, a thermometer, and a constant pressure dropping funnel. Add a 38% formaldehyde solution at 80°C, control the formaldehyde dropping speed, and add it in batches; after the addition, heat up, condense and reflux for 4 hours, connect a vacuum pump to perform reduced pressure distillation to remove water, and gradually increase the vacuum degree in the reaction flask. When the fraction is small, increase the temperature in the reaction flask to 150°C, stop distillation, and obtain the modified amine curing agent.

[0059] In this embodiment, the molar ratio of m-xylylenediamine, nonylphenol and formaldehyde is 1.5:1.2:0.9.

[0060] The test results of the modified amine curing agents obtained in Examples 1-3 are shown in Table 1 below:

[0061] Table 1

[0062] project index Example 1 Example 2 Example 3 Appearance Yellow transparent liquid pass pass pass Viscosity, 25°C 2000-4000cp 3500 2500 3500 Gel time, 25℃, min ≤30min 20 15 20

[0063] It can be seen from Table 2 that the modified amine curing agent prepared in Example 2 has a lower viscosity and a shorter drying time, and is preferably used as a modified amine curing agent for testing.

[0064] Embodiment 4-8

[0065] A preparation method of a chelated solvent-free low-surface nano heavy anticorrosion coating is as follows:

[0066] The preparation method of component A is as follows:

[0067] 1) Add 10-15 parts of active diluent and 0.5-0.9 parts of dispersant into a batching kettle, stir at 700 rpm for 5 minutes until uniformly dispersed; add 20-40 parts of epoxy resin, stir at 600 rpm for 3 minutes until uniformly dispersed;

[0068] 2) Add 0.5-1.5 parts of rheological additive, disperse at 1000 rpm for 20 minutes, control the temperature at 45°C, and stop and keep warm for 30 minutes;

[0069] 3) Add 10-20 parts of anti-rust pigment and 10-20 parts of nano filler, stir at 1000 rpm for 30 minutes, and disperse to a fineness of less than 60 μm;

[0070] 4) Add 10-20 parts of flaky filler, 0.1-0.5 parts of defoaming agent, and 1-4 parts of chelating agent, and stir at 1000 rpm for 5 minutes until the mixture is evenly dispersed to obtain component A;

[0071] When in use, the components A and B are evenly mixed in a weight ratio of 5:1 to obtain a chelating type solvent-free low-surface nano heavy anti-corrosion coating.

[0072] The composition ratios of the chelating solvent-free low-surface nano heavy-duty anti-corrosion coatings prepared in Examples 4-8 are shown in Table 2.

[0073] Table 2

[0074]

[0075] Test according to Table A.0.2 and the following standards in GB / T50393-2017, where the construction test temperature range is -5℃ to 40℃, and observe the surface and dry state after 24 hours. When testing water curing, the ambient humidity is greater than 100%.

[0076] The product properties of Examples 4-8 are shown in Table 3:

[0077] Table 3

[0078]

[0079]

[0080] According to the above embodiments, it can be found that the chelating solvent-free low-surface nano heavy anti-corrosion coating has excellent construction performance and is not afraid of water or rust on the substrate; at the same time, the paint film has excellent wear resistance, adhesion, flexibility and impact resistance, density, excellent shielding performance, and excellent acid, alkali and corrosion resistance; the VOC content is lower than 5g / L, which is safe and environmentally friendly.

[0081] Figure 3 The salt spray resistance test results of the coating obtained in Example 6 show that the coating has good anti-corrosion performance. Figure 5 After the coating prepared in Example 7 is sprayed, water is continued to be sprayed to observe the curing of the coating. It can be seen that the coating can be applied with water without affecting the curing of the coating.

[0082] Referring to Example 6, the type of curing agent was changed, and the comparative curing agents selected were Meidong 650, Naisol 730, Card Le LITE 3040, forming comparative examples 1-3, and their compositions and performance tests are shown in Tables 4-5 respectively.

[0083] Table 4

[0084]

[0085]

[0086] Table 5

[0087]

[0088]

[0089] Through the above comparative examples, it can be found that the present invention has better anti-corrosion performance and construction performance than similar products on the market, especially on the surface of water and rusted substrates.

[0090] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.

Claims

1. A chelated solvent-free low surface nano heavy anti-corrosion coating, characterized in that: It comprises component A and component B, wherein the weight ratio of component A to component B is 4-6:1; the raw materials of each component and the weight proportion of each raw material are as follows: Component A: 20-40 parts of epoxy resin, 10-15 parts of active diluent, 0.5-0.9 parts of dispersant, 0.5-1.5 parts of rheological additive, 0.1-0.5 parts of defoamer, 10-20 parts of anti-rust pigment, 10-20 parts of flake filler, 10-20 parts of nano filler, 1-4 parts of chelating agent; Component B: 100 parts of modified amine curing agent.

2. The chelate-type solvent-free low-surface nano heavy anti-corrosion coating according to claim 1, characterized in that: The preparation method of the modified amine curing agent is as follows: m-phenylenediamine and nonylphenol are uniformly mixed and reacted with formaldehyde solution under condensation reflux conditions, water is removed by reduced pressure distillation during the reaction, and finally a high temperature reaction is performed to obtain the modified amine curing agent.

3. The chelate-type solvent-free low-surface nano heavy anti-corrosion coating according to claim 2, characterized in that: The molar ratio of m-phenylenediamine, nonylphenol and formaldehyde is 1.2-1.6:1.0-1.4:0.6-1.0; and the mass concentration of the formaldehyde solution is 36-38%.

4. The chelate-type solvent-free low-surface nano heavy anti-corrosion coating according to claim 2, characterized in that: The temperature of condensation reflux is 90-110°C, and the reaction time is 3.5-4h; the temperature of high temperature reaction is: 140-150°C.

5. The chelate-type solvent-free low-surface nano heavy anti-corrosion coating according to claim 1, characterized in that: The epoxy resin is a liquid epoxy resin, such as one or more of Phoenix 618, Nan Ya 128, Sanmu 828, and Sanmu 827; the active diluent is a bifunctional active diluent, such as one or more of Naisu RAL602, Purkai PRO-602, and Yuanbang HK-622.

6. The chelate-type solvent-free low-surface nano heavy anti-corrosion coating according to claim 1, characterized in that: The dispersant is BYK9076; the rheological additive is Arkema wax powder Crayvallac SLT; and the defoaming agent is Deqian 6800.

7. The chelate-type solvent-free low-surface nano heavy anti-corrosion coating according to claim 1, characterized in that: The anti-rust pigment is one or more of zinc phosphate, aluminum tripolyphosphate, zinc phosphomolybdate, red iron, and mica iron oxide; the flake filler is flaky glass flakes with a thickness of 5 microns.

8. The chelate-type solvent-free low-surface nano heavy anti-corrosion coating according to claim 1, characterized in that: The nano filler is one or more of nano zinc oxide, nano iron oxide, nano titanium oxide and nano sodium silicate.

9. The chelate-type solvent-free low-surface nano heavy anti-corrosion coating according to claim 1, characterized in that: The chelating agent is the German Schwegmann rust converter Korrodur.

10. A method for preparing the chelating solvent-free low-surface nano heavy anticorrosive coating according to claim 1, characterized in that: The preparation method comprises the following steps: The preparation method of component A is as follows: 1) Add 10-15 parts of active diluent and 0.5-0.9 parts of dispersant into a batching kettle, stir at 500-700 rpm for 3-5 minutes until uniformly dispersed; add 20-40 parts of epoxy resin, stir at 300-600 rpm for 3-5 minutes until uniformly dispersed; 2) Add 0.5-1.5 parts of rheological additive, disperse at 1000-1500 rpm for 20 minutes, control the temperature at 40-55°C, and stop to keep warm for 30 minutes; 3) Add 10-30 parts of filler, 10-20 parts of anti-rust pigment, and 10-20 parts of nano filler, stir at 800-1000 rpm for 30 minutes, and disperse to a fineness of less than 60 μm; 4) Add 10-20 parts of flaky filler, 0.1-0.5 parts of defoaming agent, and 1-4 parts of chelating agent, and stir at a speed of 600-1000 rpm for 5-10 minutes until uniformly dispersed to obtain component A; When in use, the components A and B are mixed evenly in a weight ratio of 4-6:1 to obtain a chelating type solvent-free low-surface nano heavy anti-corrosion coating.

Citation Information

Patent Citations

  • Solvent-free flexible anticorrosion epoxy coating material, preparation method thereof and using method thereof

    CN103788735A

  • High-toughness hydrophobic epoxy hardener and preparation method thereof

    CN105542129A

  • Rust anticorrosive paint and preparation method thereof

    CN115746666A

Cited By

  • Water-based heavy-duty anti-corrosion coating for coating rust and residual paint film

    CN122037741A